Cytoreductive nephrectomy and exposure to sunitinib – a post hoc analysis of the Immediate Surgery or Surgery After Sunitinib Malate in Treating Patients With Metastatic Kidney Cancer (SURTIME) trial. (24th November 2021) - Abu‐Ghanem, Yasmin; van Thienen, Johannes V.; Blank, Christian; Aarts, Maureen J. B.; Jewett, Michael; de Jong, Igle Jan; Lattouf, Jean‐Baptiste; van Melick, Harm H. E.; Wood, Lori; Mulders, Peter; Rottey, Sylvie; Wagstaff, John; et al.
Abstract: Objective: To analyse if exposure to sunitinib in the Immediate Surgery or Surgery After Sunitinib Malate in Treating Patients With Metastatic Kidney Cancer (SURTIME) trial, which investigated opposite sequences of cytoreductive nephrectomy (CN) and systemic therapy, is associated with the overall survival (OS) benefit observed in the deferred CN arm. Patients and Methods: A post hoc analysis of SURTIME trial data. Variables analysed included number of patients receiving sunitinib, time from randomisation to start sunitinib, overall response rate by Response Evaluation Criteria In Solid Tumors (RECIST) version 1.1, and duration of drug exposure and dose in the intention‐to‐treat population of the immediate and deferred arm. Descriptive methods and 95% confidence‐intervals (CI) were used. Results: In the deferred arm, 97.7% (95% CI 89.3–99.6%; n  = 48) received sunitinib vs 80% (95% CI 66.9–88.7%, n  = 40) in the immediate arm. Following immediate CN, 19.6% progressed 4 weeks after CN and the median time to start sunitinib was 39.5 vs 4.5 days in the deferred arm. At week 16, 46.0% had progressed at metastatic sites in the immediate CN arm vs 32.7% in the deferred arm. Sunitinib dose reductions, escalations and interruptions were not statistically significantly different between arms. Among patients who received sunitinib in the immediate or deferred arm the median total sunitinib treatment duration was 172.5 vs 248 days. Reduction of target lesions was more profound in the deferred arm. Conclusions: In comparison to the deferred CN approach, immediate CN impairs administration, onset, and duration of sunitinib. Starting with systemic therapy leads to early and more profound disease control and identification of progression prior to planned CN, which may have contributed to the observed OS benefit.